DETERMINAN DISMENOREA DI SMAN 2 BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Juliana, Juliana (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
Dysmenorrhea is one of gynecological disorder which commonly found in women. The preliminary survey at SMAN 2 Bagan Sinembah revealed that many female students were absent from school because of suffering from dysmenorrhea. The objective of the research was to identify the determinants of the factors which were correlated with dysmenorrhea at SMAN 2 Bagan Sinembah, Rokan Hilir Regency, in 2016. The research used cross sectional designand 141 of them were used as the samples. The research variables were anemia, the habit of doing sport, history of family, and nutritional status. The data were analyzed by using univariate analysis, bivariate analysis, and multivariate analysis with logistic regression test. The result of bivariate analysis showed the variables of anemia (p=<0.000), the habit of doing sport (p=<0.000), history of family (p=<0.000), and nutritional status (p=<0.000), while the result of multivariate analysis showed that nutritional status had p-value=0.000 (p<0.05), OR=5,508 (95% CI; 2.842-23.824). The conclusion was that there was the correlation of anemia, the habit of doing sport, history of family, and nutritional status with dysmenorrhea. The factor which had the most dominant correlation was nutritional status. The respondents should improve their knowledge of determinants of dysmenorrhea, either from their eating pattern or from their habitual actionsDismenorea atau nyeri haid merupakan salah satu keluhan ginekologi yang paling umum pada perempuan muda. Berdasarkan survey pendahuluan yang peneliti lakukan di SMAN 2 Bagan Sinembah banyak siswi yang izin tidak masuk sekolah, dan alasan yang didapat oleh peneliti mereka izin tidak masuk sekolah dikarenakan dismenorea yang mereka alami. Penelitian ini bertujuan untuk mengidentifikasi determinan faktor-faktor yang berhubungan dengan dismenorea di SMAN 2 Bagan Sinembah Kabupaten Rokan Hilir Tahun 2016. Penelitian ini menggunakan desain cross sectional dengan jumlah sampel sebanyak 141 orang. Variabel dalam penelitian ini adalah, anemia, kebiasaan olahraga, riwayat keluarga dan status gizi. Analisis data digunakan secara bertahap mencakup analisis univariat, analisis bivariat, serta analisis multivariat dengan uji regresi logistik. Hasil analisis bivariat diperoleh variabel anemia (p=<0,000), kebiasaan olahraga (p=<0,000), riwayat keluarga (p=<0,000) dan status gizi (p=<0,000), sedangkan analisis multivariat menunjukkan status gizimemiliki nilai p=0,000 (p<0,05), OR = 5,508 (95% CI; 2,842-23,824). Kesimpulannya adanya hubungan anemia, kebiasaan olahraga, riwayat keluarga dan status gizi dengan dismenorea, serta faktor yang paling dominan adalah status gizi. Disarankan kepada responden untuk lebih menambah pengetahuannya tentang determinan dismenorea baik dari segi menjaga pola makanannya serta kebiasaan yang dilakukannya.